Agriculturalization as a syndrome : a comparative study of agriculture in Argentina and Australia - Young, Sarah (UN SantiagoCL, 2006)
Examines the potential syndrome of agriculturalization as it occurs in Argentina and attempts to draw parallels to the case of agriculture and environmental degradation in Australia.